2009
DOI: 10.1158/0008-5472.can-09-0016
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nectin-4 Oncoprotein as a Diagnostic and Therapeutic Target for Lung Cancer

Abstract: Gene expression profile analysis of lung cancers revealed the transactivation of an immunoglobulin-like molecule Nectin-4 in the majority of non-small cell lung cancers (NSCLC). Immunohistochemical staining of 422 NSCLCs showed that a high level of Nectin-4 expression was associated with poor prognosis for NSCLC patients (P < 0.0001), and multivariate analysis confirmed its independent prognostic value (P < 0.0001). We established an ELISA to measure serum Nectin-4 and found that serum Nectin-4 levels were sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
175
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(199 citation statements)
references
References 49 publications
7
175
2
Order By: Relevance
“…Generally, we observed similar overall frequency of nectin-4 expression in ovarian cancer as previously published by Derycke and colleagues (26). Soluble form of Nectin-4 in patient serum and in ascites in case of ovarian cancer has been reported (24)(25)(26). Although the levels varied between reports, all investigators show an association between higher detected levels of soluble nectin-4 and disease progression.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Generally, we observed similar overall frequency of nectin-4 expression in ovarian cancer as previously published by Derycke and colleagues (26). Soluble form of Nectin-4 in patient serum and in ascites in case of ovarian cancer has been reported (24)(25)(26). Although the levels varied between reports, all investigators show an association between higher detected levels of soluble nectin-4 and disease progression.…”
Section: Discussionsupporting
confidence: 88%
“…More recently, nectin-4 was identified as an entry point for measles and other viruses and was proposed as a target for oncolytic viral therapy (21,22). Although several groups reported the detection of nectin-4 expression in breast, ovarian, and lung cancers (23)(24)(25)(26), no comprehensive analysis has been reported to date. Using suppression subtractive hybridization, we identified nectin-4 as one of the genes dramatically upregulated in bladder cancer specimens.…”
Section: Discussionmentioning
confidence: 99%
“…With accumulating data indicating occludin as an essential player in apoptotic signaling following TJ disruption and its downregulation predisposing to metastatic behaviors in vitro and in vivo, it is exciting to speculate that re-expressing occludin in cancer may act as a potential therapeutic target. In support, a previous in vitro study demonstrated how reexpression of occludin (in occludin-absent oncogene-transformed cells) was sufficient to restore the appearance of a normal epithelial phenotype (65). Though no clinical trials are currently underway, emerging research might potentially focus upon the epigenetic regulation of occludin via TTF-1 and other activators as a promising strategy to correct the deficits associated with occludin loss in cancer.…”
Section: Occludinmentioning
confidence: 79%
“…Normally, nectins 1, 2 and 3 show abundant expression in adult tissues, but nectin-4 is primarily expressed in the embryo and the placenta (Reymond et al, 2001;Fabre-Lafay et al, 2007). Nectin-4 has been shown to be a specific tumour-associated marker for ductal mammary carcinoma, lung adenocarcinoma and ovarian carcinoma in humans (Fabre-Lafay et al, 2007;Takano et al, 2009;Derycke et al, 2010). Studies in humans and experimental animal models have shown that nectin-4 is a valuable biomarker for evaluating tumour progression and the metastatic status of carcinomas (Fabre-Lafay et al, 2007;Oshima et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Nectin-4 is a type I transmembrane glycoprotein which has recently proven to be overexpressed in human breast carcinoma and is thus considered a specific tumour-associated marker, as the normal mammary gland lacks nectin-4 expression (Fabre-Lafay et al, 2007). In non-small cell lung cancer, a high level of nectin-4 expression has been shown to be associated with a poor prognosis (Takano et al, 2009). …”
mentioning
confidence: 99%